2017
DOI: 10.3389/fpsyg.2017.01700
|View full text |Cite
|
Sign up to set email alerts
|

Age-Based Positivity Effects in Imagining and Recalling Future Positive and Negative Autobiographical Events

Abstract: Thoughts about the future reflect personal goals, and projections into the future enrich our emotional life. Researchers have taken an interest in determining whether the tendency to remember more positive than negative emotional events observed when recalling past events also appears when remembering imagined future events. The objective of this study was to examine the age-based positivity effect of recall for future positive and negative autobiographical events in young and older adults. Representative futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 74 publications
(110 reference statements)
2
14
0
Order By: Relevance
“…Thus, positivity effect means that, compared to young people, older people react less to negative situations and preferentially attend to and recall emotionally meaningful and positive stimuli ( Reed et al, 2014 ). This positivity effect has been observed with a multitude of materials such as scenes, drawings, and faces (e.g., Charles et al, 2003 ; Mather and Carstensen, 2005 ; Reed et al, 2014 ; Mammarella et al, 2016 ), words ( Kensinger, 2008 ; Hamilton and Allard, 2020 ), or autobiographical experiences of the past and recreations of the future ( Berntsen and Jacobsen, 2008 ; Gallo et al, 2011 ; Cole et al, 2016 ; García-Bajos et al, 2017 ). Older people not only show a greater preference for the positive than young people, but they also generate false memories or transform and modify negative content to make it more positive and, thus, achieve greater consistency with their emotional goals and motivations, and higher emotion regulation and well-being ( Charles et al, 2003 ; Carstensen et al, 2020 ; Zaragoza Scherman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, positivity effect means that, compared to young people, older people react less to negative situations and preferentially attend to and recall emotionally meaningful and positive stimuli ( Reed et al, 2014 ). This positivity effect has been observed with a multitude of materials such as scenes, drawings, and faces (e.g., Charles et al, 2003 ; Mather and Carstensen, 2005 ; Reed et al, 2014 ; Mammarella et al, 2016 ), words ( Kensinger, 2008 ; Hamilton and Allard, 2020 ), or autobiographical experiences of the past and recreations of the future ( Berntsen and Jacobsen, 2008 ; Gallo et al, 2011 ; Cole et al, 2016 ; García-Bajos et al, 2017 ). Older people not only show a greater preference for the positive than young people, but they also generate false memories or transform and modify negative content to make it more positive and, thus, achieve greater consistency with their emotional goals and motivations, and higher emotion regulation and well-being ( Charles et al, 2003 ; Carstensen et al, 2020 ; Zaragoza Scherman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…However, there are important differences between thinking about the past and imagining the future. Although both situations involve the recreation and enjoyment of pleasant thoughts and the uncomfortable anticipation of fears and concerns, it has been observed that thoughts about future experiences are more positive than past events ( Berntsen and Rubin, 2002 ; Berntsen and Jacobsen, 2008 ; García-Bajos et al, 2017 ; Zaragoza Scherman et al, 2020 ). Interestingly, according to aging literature, older people tend to remember their past more positively ( Kennedy et al, 2004 ; Schryer and Ross, 2014 ) and to perceive their future as more idyllic and positive compared to young people (e.g., Berntsen and Rubin, 2002 ; Burr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideas put forward by the participants also support the notion that people may be motivated to stop the retrieval of memories that generate fear, concern or sadness, a blockage that shows the defensive capacity of the self to prevent thoughts that break down personal balance (Conway et al, 2004). Consistent with this idea, inhibitory processes can modulate the accessibility of negative thoughts and episodes and may help keep negative memories from coming to mind (García-Bajos et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…In any event, medical content generally involves disturbing or negative information that we do not want to remember. Recent research shows that we tend to block or forget negative events (García-Bajos & Migueles, 2017; García-Bajos, Migueles, & Aizpurua, 2017; Szpunar, Addis, & Schacter, 2012).…”
Section: Memory Of Medical Scenarios In the Life Support Preferences Questionnairementioning
confidence: 99%